Who are Canada's temporary foreign workers? Policy evolution and a pandemic reality. (4th February 2022) - Akbar, Marshia
Abstract: Since the late‐2000s, Canada has admitted an increasing number of foreign workers with a wide range of temporary work permits to meet local labour shortages and growing labour market demands. Unlike permanent residents, temporary residents are subjected to restricted work authorizations and social citizenship rights. Besides, Canadian policies distinguish different groups of temporary foreign workers based on their skill level and work permit type to determine their eligibility for employment, social rights and permanent residency. Reviewing secondary sources, this paper contributes to analyzing the key policies that have shaped the diverse streams within the Canadian temporary migration program. The analysis also highlights the inequalities experienced by various categories of temporary foreign workers in Canada and assesses these inequalities within the context of the COVID‐19 pandemic.